Neotypification of Fleminigia rollae (Leguminosae) - Gavade, Sandip K; Lekhak, Manoj M (Phytotaxa, 2015)
The genus Flemingia Roxburgh ex Aiton (1812: 349) (Leguminosae) comprises ca. 37 species and seven varieties distributed in the world (The Plant List 2013). In India, 17 species and one variety are reported, of which five species and one variety are endemic (Sanjappa 1992).